IMPLEMENTASI MANAJEMEN TENAGA KEPENDIDIKAN DALAM PENINGKATAN PROFESIONALISME TENAGA KEPENDIDIKAN - astuti, kuntari puji; noor, marzuki; andayani, sutrisni (Universitas Muhammadiyah Metro, 2023)
ABSTRACT One indicator of increasing the professionalism of teaching staff at Darul A’mal Metro vocational school is the development of planning, organizing and controlling at the end of each semester. The goal to be achieved in this study is to find out the management of professionalism of educational staff. This research is a qualitative descriptive study. The number of educational staff is 11 people at Darul A’mal Metro Lampung vocational school all of whom are sampled. Collecting data using interviews and observation. The data analysis used is a phenomenological study related to concepts, opinions, and attitudes. The results pf the study show the implementation of educational staff management in increasing the professionalism of educational staff in development of planning, organizing and controlling education staff in professionalism. The educational staff management variable contributes together to the educational staff professionalism variable. While others are explained by other factors not examined in this study. Keywords: management, educational staff, profesinalism